2014
DOI: 10.1371/journal.pone.0088341
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Unsaturated Fatty Acids and Ergosta-7,22-dien-3-ol from Marthasterias glacialis: Prevention of CHOP-Mediated ER-Stress and NF-κB Activation

Abstract: There has been increasing awareness to the potential interest of drug discovery from marine natural products to treat several pathological conditions, including inflammation. In this work we describe the anti-inflammatory activity of several compounds present in the echinoderm Marthasterias glacialis (spiny sea-star), using the inflammatory model RAW 264.7 cells challenged with LPS. Lipidomic profiling of the organism revealed two major classes of compounds: fatty acids and sterols. Among these, the predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 24 publications
1
43
0
1
Order By: Relevance
“…In fact, marine organisms present a huge diversity and live in complex habitats exposed to extreme conditions becoming, in this way, a unique source of bioactive compounds, which cannot be found in other organisms. 3 Among them we can highlight the presence of long-chain polyunsaturated fatty acids (PUFA), especially those with three or more double bonds, which are a class of lipids characteristic of marine organism with important bioactivities. 2 For example, research developed by our group showed that the echinoderm Marthasterias glacialis (spiny sea-star) contains a big amount of fatty acids, being an interesting source of anti-inammatory molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, marine organisms present a huge diversity and live in complex habitats exposed to extreme conditions becoming, in this way, a unique source of bioactive compounds, which cannot be found in other organisms. 3 Among them we can highlight the presence of long-chain polyunsaturated fatty acids (PUFA), especially those with three or more double bonds, which are a class of lipids characteristic of marine organism with important bioactivities. 2 For example, research developed by our group showed that the echinoderm Marthasterias glacialis (spiny sea-star) contains a big amount of fatty acids, being an interesting source of anti-inammatory molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Marine-derived molecules have been a prolific source of new anti-inflammatory drugs [11,12,13], reason for which we have conducted screening studies on the anti-inflammatory activity of the aqueous extracts of both sea anemones and their major metabolite, the alkaloid homarine.…”
Section: Resultsmentioning
confidence: 99%
“…In this situation, macrophages present a number of biochemical traits, such as increased production of NO via inducible nitric oxide synthase (iNOS) [11] and increased levels of intracellular ROS.…”
Section: Resultsmentioning
confidence: 99%
“…Cell viability was evaluated by the MTT reduction assay . After incubation (24 h), MTT (final concentration 0.5 mg/ml) was added to each well and the plate was incubated for 2 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%